An Intelligent Contract-Driven Bidding Approach for Electric Vehicle Aggregators to Facilitate Blockchain-Powered Energy Trading - Imran Hussain; Hafiz Ashiq Hussain; Nasim Ullah; Stanislav Misak (IEEE Access)
The integration of aggregators into the market and peer-to-peer energy trading of electric vehicles achieved through blockchain technology represents one of the potential ways to ensure peer privacy preservation, transaction trackability, and greater energy system flexibility. This paper presents a decentralized blockchain-powered smart contract-based peer-to-peer model to enable optimal energy trading coordination of electric vehicles with aggregators in the smart community, where revenue from feed-in tariffs, ancillary services, and peer-to-peer sales are optimized, and the cost is minimized using a mixed-integer linear programming formulation. The goal of the real-time bilateral trading scheme is to balance supply and demand within the constraints of the power network through direct peer-to-peer negotiations without the need for a middleman. The performance evaluation of the proposed scheme demonstrates how well the framework synchronizes power supply and demand by coordinating electric vehicles’ charging and discharging through an appropriate aggregator by consumption patterns. The development of smart contracts for initiation, enrollment, stay-alive negotiation, trading, and settlement of transactions is presented in the subsequent demonstration of the blockchain model’s distinctive establishment process. Furthermore, the transactional efficiency depicting the execution time, latency, and throughput performance for viability and scalability evaluations in practical applications is presented to illustrate the effectiveness of the proposed framework.